IDENTIFIKASI SOSIAL BUDAYA IBU TERHADAP FAKTOR RESIKO KEJADIAN DIARE PADA BALITA - Yarmaliza (Universitas Prima Indonesia, 2020)
One of the infectious diseases that is still a public health problem in indonesia is diarrhoea, this is because the rate of pain and death is still high and always fluctuates every year. The scope of the treatment of cases of diarrhea in Aceh Province in 2017 showed that of the 140,116 estimated cases of diarrhea found only 83,914 patients were treated or 59.9 %. Then in 2018 the coverage of the service estimated diarrhea in health facilities 95,924 with the number of people with diarrhea found only 25,724 were treated or by 26.82%. The purpose of the research to know the characteristics factors of the mother ( education and knowledge of the mother) against the occurrence of diarrhea in toddlers in the working area of the health center suak ribee. The research method is done with cross sectional approach, retrieval technique using Simple Random Sampling. The sample was taken according to the inclusion criteria of 91 respondents. Data analysis includes univariate and bivariate analysis using Chi-Square Test. The results of statistical analysis with chi Square correlation test technique show that maternal education and knowledge have a relationship to the incidence of diarrhea in toddlers (P.Value <0.05). The conclusion is that there is a relationship between education and knowledge of mothers with risk factors for the incidence of diarrhea in children under five, It is recommended for further research to look further at other risk factors for the incidence of diarrhea in toddlers.